2002
DOI: 10.1046/j.1365-3156.2002.00900.x
|View full text |Cite
|
Sign up to set email alerts
|

First nationwide survey of the health of schoolchildren in Chad

Abstract: SummarySurvey data are presented from a nationwide survey of the health of schoolchildren in Chad. The country was stratified into distinct ecological zones based on satellite sensor environmental data. Twenty schools were visited and 1024 children aged between 6 and 15 years were included in the study. The overall prevalence of stunting, underweight, anaemia and goitre was 18.7, 16.5, 25.1 and 23.3%, respectively. Schistosoma haematobium, Schistosoma mansoni and hookworm were the only helminth species found w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
4
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 8 publications
2
15
4
1
Order By: Relevance
“…For the peripheral neighbourhoods of the capital N'Djamena, a S. haematobium infection prevalence of 11.8% was reported in the mid-1990s (Massenet et al, 1995). For N'Djamena itself, a prevalence of 2.6% for S. haematobium (Beasley et al, 2002) and nil for S. mansoni (Alio et al, 2013) have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the peripheral neighbourhoods of the capital N'Djamena, a S. haematobium infection prevalence of 11.8% was reported in the mid-1990s (Massenet et al, 1995). For N'Djamena itself, a prevalence of 2.6% for S. haematobium (Beasley et al, 2002) and nil for S. mansoni (Alio et al, 2013) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A national survey carried out in 2000 revealed a coun-try-wide prevalence of 13.2% for S. haematobium and 1.0% for S. mansoni among school-aged children (Beasley et al, 2002). More recently, Alio et al (2013) reported a somewhat higher prevalence of 3.4% for S. mansoni.…”
Section: Introductionmentioning
confidence: 99%
“…This association is not a simple causal one because complex environmental, social and economic factors interfere [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…However, data on the growth of school-age children, generated in a consistent manner across countries and over time, is difficult to find [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Brown (1994) and Appleton (1978) documented the climate and environmental variables that influenced the distribution of schistosomiasis. GIS was used in a larger scale schistosomiasis study in Asia (Cross et al 1996, Seto et al 2002, Yang et al 2005, Zhang et al 2008) and in several African countries, including Ethiopia , Egypt (Abdel-Rahman et al 2001, Malone et al 1994, Uganda (Kabatereine et al 2004), Tanzania (Brooker et al 2001) and Chad (Beasley et al 2002, Brooker 2002). In the state of Bahia, Brazil, Bavia et al (2001) conducted one of the first studies that attempted to correlate disease distribution with environmental variables.…”
Section: Utilization Of the Geographical Information Systemmentioning
confidence: 99%